(untitled) (Research, Society and Development, 2022)
This study is a research clipping that is being carried out in the Postgraduate Program - Master in Teaching, PPGE/UNIC/IFMT, whose main objective is to understand the motivations and meanings that Youth and Adult Education students (EJA) expose about their permanence in school. The present research was carried out in two state public schools in the city of Cuiabá and the data collection took place through a semi-structured interview applied to eleven students of the 1st segment of the EJA. This is an exploratory qualitative investigation that uses documentary sources and interviews. We present as partial results, the difficulty of the labor market/schooling, due to economic needs, as well as family issues. Therefore, we believe that this research based on the students’ narratives will help to understand more clearly the students’ behavior, their challenges, their individual experiences, which involve their personality, values, ideologies, anxieties among others. We conclude, therefore, that the study of EJA is not limited by workload, but by development within the possibilities of each student. The central idea of ​​this research focuses on provoking new reflections and new possibilities of interpretation that can favor the teaching-learning process of EJA students.